Analysis of the Implementation of the Regional Property Management System on the Financial Reports of the Musi Banyuasin District Health Service 2020 - Alexander, Alexander; Sunarsih, Elvi; Setiawan, Arum; Novitrie, Ayu (MSJ : Majority Science Journal, 2024)
Regional property (BMD) is very important for government operations, especially in terms of providing services to the community. The government must re-examine the management of regional property assets to ensure that they are in accordance with applicable laws and regulations and have good financial reports. This study aims to evaluate the use of the regional property management system in the financial statements of the health department of Musi Banyuasin Regency. This study was designed as an analytic survey with a cross-sectional design. This study involved all employees in the health sector. The results showed that there was a relationship between knowledge, attitude, information technology, standard operating procedures (SOPs), and supervision on the financial statements of the Health Office of Musi Banyuasin Regency. In addition, the information technology variable is the most dominant variable on financial reports. Finally, this study suggests that the Health Office should provide complete facilities and infrastructure, including SOPs and supporting information technology, and provide training to staff.